X-ray and photo-excited luminescence of ZnWO₄ nanoparticles with different size and morphology - Tupitsyna, I.A.; Maksimchuk, P.O.; Yakubovskaya, A.G.; Malyukin, Y.V.; Zvereva, V.S.; Vovk, O.M. (Functional Materials, 2016)
X-ray and photoluminescence of ZnWO₄ nanocrystals with controlled size and morphology: grains with diameter of 10-20 nm; rods with diameter of 10-20 nm and length of 200-250 nm produced by microwave hydrothermal method were studied. Red luminescence with λmax = 700 nm was found in the samples. The intensity of the red luminescence increases with decreasing of the ZnWO₄ nanoparticles size due to increase of concentration of oxygen vacancies and creation of distorted WO₆ centers. It was shown that reduction in the X-ray luminescence intensity with decrease of the ZnWO₄ nanoparticles size is due to creation of the distorted WO₆ centers which are the nonradiative relaxation channel competing with the self-trapped excitons.